1158 Women health and work. (24th April 2018) - Kumar, Ravindra; Patil, Pragati; Mishra, Shriniket; Singh, Anoop
Abstract : Introduction: India, Women working on shop floor is new concept for Automobile industries. women taking up tools to partake in manufacturing of two-wheelers, hitherto a male bastion. As the call for women empowerment gets louder, Automobile two-wheeler manufacturers are responding with an aim to create a culture where women can stand shoulder to shoulder with their male counterparts to contribute to the growth of the company. Occupational health Centre is concerned about their health, a cross-sectional scientific study conducted in an automobile industry to assess Body Mass Index with an aim to make healthy work pattern suitable to their physiology. Method: Study was conducted on 27 randomly selected unmarried women work team member in age group of 19–24 years of frame assembly section in an automobile industry. Job was working on assembly line of two wheeler of automobile manufacturing industry. Parts pick from conveyor tray and to mounting on frame body of two-wheeler. Measure the weight and height and then calculate the BMI of the team member were computed at the time of joining and after 6 month of staring work, general clinical check-up including heart rate, and oxygen saturation and BP monitoring before and after the 6 month interval of work schedule. Results: Women working on shop floor mean age 21.5 years, mean weight 44.40 kg and mean height 161.66 cm and mean BMI 18.28 taking balance and with 8 hours shift duty, leave as per prorota basis, 48 hours work in one week. Review periodical medical examination after 6 month found mean height 161.66 and mean weight 50.30 kg and mean BMI 20.88. Conclusion: This is first surveillance of women health status in automobile industry in India under occupational health physician. Taking balance diet with structured work pattern with appropriate work atmosphere result in improved average BMI.